Anti-tumor effect of dandelion flavone on multiple myeloma cells and its mechanism - Gui, Hua; Fan, Xiaohong (Discover. Oncology, 2024)
Background Multiple myeloma (MM) is a prevalent hematologic malignancy characterized by the uncontrolled proliferation of monoclonal plasma cells in the bone marrow and excessive monoclonal immunoglobulin production, leading to organ damage. Despite therapeutic advancements, recurrence and drug resistance remain significant challenges. Objective This study investigates the effects of dandelion flavone (DF) on MM cell proliferation, migration, and invasion, aiming to elucidate the mechanisms involved in MM metastasis and to explore the potential of traditional Chinese medicine in MM therapy. Methods DF's impact on myeloma cell viability was evaluated using the CCK-8 and colony formation assays. Cell mobility and invasiveness were assessed through wound healing and transwell assays, respectively. RT-PCR was employed to quantify mRNA levels of MMP-2, MMP-9, TIMP-1, and TIMP-2. Apoptotic rates and molecular markers were analyzed via flow cytometry and RT-PCR. The PI3K/AKT signaling pathway was studied using Western blot and ELISA, with IGF-1 and the PI3K inhibitor LY294002 used to validate the findings. Results DF demonstrated dose-dependent inhibitory effects on MM cell proliferation, migration, and invasion. It reduced mRNA levels of MMP-2 and MMP-9 while increasing those of TIMP-1 and TIMP-2. Furthermore, DF enhanced the expression of pro-apoptotic proteins and inhibited M2 macrophage polarization by targeting key molecules and enzymes. The anti-myeloma activity of DF was mediated through the inhibition of the PI3K/AKT pathway, as evidenced by diminished phosphorylation and differential effects in the presence of IGF-1 and LY294002. Conclusion By modulating the PI3K/AKT pathway, DF effectively inhibits MM cell proliferation, migration, and invasion, and induces apoptosis, establishing a novel therapeutic strategy for MM based on traditional Chinese medicine.